A randomized, double-blind, placebo-controlled phase I trial of inhalation treatment of recombinant TFF2-IFN protein: A multifunctional candidate for the treatment of COVID-19 - Liu, Yan; Zhai, Guanxing; Fu, Weihui; Zhang, Xiaoyan; Xu, Jianqing (Frontiers in Pharmacology, 2022)
Background and Objectives: Coronavirus disease 2019 (COVID-19) caused global pandemics during last three years, the development of new therapeutics is urgently needed. To assess the safety, well-tolerated, and featured with prolonged retention in respiratory tract of recombinant protein TFF2-IFN in healthy volunteers. Methods: We conducted a randomized, double-blind, placebo-controlled, single-dose, dose-escalation Phase Ⅰ study to evaluate the safety, tolerability, pharmacokinetics (PK) and cytokine responses after the administration of the recombinant TFF2-IFN proteins. Healthy volunteers were informed, enrolled and randomized into 4 groups with a dose escalation of 0.2, 1, 2, 4 mg/per dose, and then inhaled with the investigation product (IP) or placebo. 32 eligible participants were finally enrolled, 8 were assigned to placebo group and 24 to TFF2-IFN groups with 6 participants per group. Data were collected from Nov 19, 2021 to Jan 4,2022. Results: All 32 participants completed the study. 41.7% (10/24) of participants who received recombinant TFF2-IFN protein reported 11 AEs during treatment, and 62.5% (5/8) of participants who received placebo reported 6 AEs. 16 out of total 17 AEs were Grade 1 in severity. Only one Grade 3 AE was occurred in placebo group, and no worse event happened as SAE. The PK were analyzed for the times and concentrations of investigation product in 0.2, 1, 2, 4mg groups in 24 TFF2-IFN recipients, the results showed that TFF2-IFN retains in the lung for at least 6-8 hours, only the highest dose group (4mg/per) has a transient detectable concentration in sera, whereas all other dose groups had a level below the lower limit of quantification (LLOQ). In addition, only IFN-gamma was detectable and none of inflammatory cytokines appeared in sera. Conclusion: In the study, the recombinant TFF2-IFN protein was a well-tolerated and safe therapeutics when administrated through nebulization, featured with prolonged retention in respiratory tract which will be greatly beneficial to combat against respiratory viral infection.